Information asymmetry, financialisation and financial access - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
This study investigates whether information sharing channels that are meant to reduce information asymmetry have led to an increase in financial access. The study employs a Generalised Method of Moments technique using data from 53 African countries during the period from 2004-2011 to examine this linkage. Information sharing channels are theoretically designed to promote the formal financial sector and discourage the informal financial sector. The study uses two information sharing channels: private credit bureaus and public credit registries. The study found that both information sharing channels have a positive and significant impact on financial access. The study also found that public credit registries complement the formal financial sector to promote financial access. The policy implications are discussed.
Keywords: G20; G29; L96; O40; O55; 330; Information asymmetry; Financialisation; Financial Access; Africa